Association Between Medication Adherence and Body Mass Index Among Elderly Patients with Hypertension: A Cross-Sectional Study - Ododai, Sitti Rafikah; Manika, Helkim S. Laode; Astuti, Widya (Bantayang Omni Cendekia, 2026)
Background: Hypertension remains a major global health problem, with a high prevalence and low treatment adherence. The World Health Organization (WHO) reports that 50-70% of patients do not adhere to antihypertensive therapy, which can hinder optimal blood pressure control. In addition, body mass index (BMI) is an important factor This study aimed to examine the association between medication adherence and body mass index among elderly patients with hypertension in the working area of the UPTD Motoboi Kecil Health Center. Methods: This study employed a quantitative analytic design with a cross-sectional approach. A total of 76 respondents were selected using purposive sampling based on predefined inclusion and exclusion criteria. Medication adherence was measured using the Morisky Medication Adherence Scale (MMAS-8), and BMI was assessed through direct measurement of weight and height. Data were analyzed using the Chi-square test to determine the association between variables. Results: The findings showed that 52.6% of respondents were categorized as non-adherent to medication, while 39.5% had underweight BMI. Statistical analysis revealed a significant association between medication adherence and BMI (p < 0.001). Conclusion: Medication adherence is significantly associated with body mass index among elderly patients with hypertension, indicating that adherence to treatment may reflect broader health behaviors influencing nutritional status. These findings highlight the importance of integrating adherence support and routine nutritional assessment into hypertension management in primary healthcare settings.